BIOSOLUBILIZATION OF PHOSPHATE ROCK BY Penicillium sp - Sri Handayani; Suratman Suratman (Puslitbang tekMIRA, 2015)
Phosphorus is an essential element that regulates soil fertility. Its deficiency is replenished by chemical fertilizer made from phosphate rock. An environmentally friendly and economically alternative to chemical processing of phosphate rock is the use of phosphate solubilizing microorganisms. In this research, a potential phosphate solubilizing fungi were successfully isolated from the surface of Cijulang phosphate rock and identified as close relative of Penicillium sp. The phosphate biosolubilization capability of the fungus was tested and the influence of leaching parameters such as particle size of mineral, ore concentration (pulp density), and initial pH of medium was investigated using a shake flask study to characterize the solubilization of phosphorus by Penicillium sp. The x-ray diffraction data indicated the presence of hydroxyl apatite Ca5(PO4,CO3)3OH as the main source of phosphorus.The fungal strains of Penicillium sp produced oxalic and citric acids during fermentation of glucose which resulted in a drop pH of the growth medium. The results also indicated a potential relationship between the phosphorus biosolubilization and the production of organic acids by the fungus. In addition, particle size, ore concentration and initial pH were also shown to have significant effects on the solubilization of phosphorus from the phosphate rock. The optimal speed of attack was obtained for a surface area of substrate of .-200 mesh. A concentration of 5% solid gave the highest speed of P biosolubilization. The optimum range of initial pH was 6-7 and initial pH began to show an inhibiting effect at 4. The maximum percentage of soluble phosphorus released of 42.8% was attained using -200 mesh particle size, 5% pulp density and initial pH 6 after 16 days of process.